Respuesta :
Answer:
(-9/2 , -10)
Step-by-step explanation:
2x-3y=21
-6x+2y=7
Multiply the first equation by 3
3(2x-3y)=21*3
6x - 9y = 63
Add this to the second equation to eliminate x
6x - 9y = 63
-6x+2y=7
------------------
0x -7y = 70
Divide by -7
-7y/-7 = 70/-7
y = -10
Now find x
2x- 3y = 21
2x -3(-10) = 21
2x +30 =21
subtract 30 from each side
2x = 21-30
2x= -9
Divide by 2
x = -9/2
(-9/2 , -10)
[tex]\underline{\bigstar{\sf\ \ Answer :-}}[/tex]
Given two equations of two variables x and y
Now lets solve it by elemination method !
[tex]:\implies\sf 2x-3y=21--------(1)\\ \\ \\ :\implies\sf -6x+2y=7-------(2)\\ \\ \\ \sf Eleminate\ (x) \\ \\ \\ \it Multiply\ first \ equation \ with \ 3\ \ \ and \ 2nd \ \ with \ 1 \\ \\ \\ :\implies\sf (2x-3y=21)\times 3 \\ \\ \\ :\implies\sf (-6x+2y=7)\times 1\\ \\ \\ :\implies\sf 6x-9y=63------(3) \\ \\ \\ :\implies\sf -6x+2y=7-----(4)\\ \\ \\ \it\ \ Add \ equation\ 3\ \ and \ 4\\ \\ \\ :\implies\sf 6x-9y=63+ (-6x+2y= 7)\\ \\ \\ :\implies\sf (6x-6x)+(-9y+2y) = 63+7\\ \\ \\ :\implies\sf 0-7y=70\\ \\ \\ :\implies\sf y= \cancel{\dfrac{70}{-7}}= - 10\\ \\ \\ :\implies\sf y= -10 [/tex]
★ Now find the value of x
let's substitute the value of y in equation 4
[tex]:\implies\sf -6x+2y=7\ \ \ \ \ \ (y= -10)\\ \\ \\ :\implies\sf -6x+2\times (-10)=7\\ \\ \\ :\implies\sf -6x-20= 7\\ \\ \\ :\implies\sf -6x = 7+20 \\ \\ \\ :\implies\sf x= \cancel{\dfrac{27}{-6}}= \dfrac{-9}{2}[/tex]
[tex]\underline{\textit{ \ \ So, \ the \ value \ of \ x\ and \ y }}[/tex]
[tex]\bigstar{\boxed{\sf x= \dfrac{-9}{2}}}[/tex]
[tex]\bigstar{\boxed{\sf\ y= (-10)}}[/tex]
